The Effect of Placement, Supervision, and Work Environment on Employee Performance at the Makassar City Communication and Informatics Office - Rusni Hasni; Akhmad; Samsul Rizal; Muhammad Ikram Idrus; Andi Mappatompo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze and test the influence of job placement, supervision, and the work environment on employee performance at the Makassar City Communication and Informatics Office. It is hypothesized that job placement, supervision, and the work environment each have a positive and significant effect on employee performance. This study employs a quantitative approach using a survey method. The population consists of all 97 employees of the Makassar City Communication and Informatics Office, with a saturated sampling technique applied, meaning the entire population is used as the sample. Data were collected through structured questionnaires distributed to respondents. The variables examined include job placement, supervision, and work environment as independent variables, and employee performance as the dependent variable. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS. The results indicate that job placement has a positive and significant effect on employee performance. Similarly, supervision shows a positive and significant influence on employee performance. The work environment also has a positive and significant effect on employee performance. These findings demonstrate that all three independent variables simultaneously and partially contribute to improving employee performance. The implications of this study suggest that organizations, particularly the Makassar City Communication and Informatics Office, should enhance human resource management practices by ensuring appropriate job placement, strengthening supervisory functions, and creating a conducive work environment. These efforts are expected to improve employee performance and ultimately enhance the quality of public services. Future research is recommended to include additional variables or broader organizational contexts to enrich the findings.